International economic policies and their theoretical foundations : a sourcebook - Letiche, John M., 1918- (Economic theory, econometrics, and mathematical economics., 1992)
The literature on international economics has become excessively specialized. In selecting distinguished readings for this source book--including contributions by Nobel laureates such as Lawrence R. Klein, Arthur Lewis, James Meade, and Theodore W. Schultz--Professor Letiche breaks the mold. The essays concentrate on interrelation between theory and actual policy design, and this collection of classic pieces and recent economic contributions are a valued resource in universities and government offices.